Weak metastability of AlxGa1−xN (x = 13/24, 15/24, 17/24) shown by analyzing AlGaN grown on AlN with dense macrosteps. (1st July 2022) - Hirano, Akira; Nagasawa, Yosuke; Ippommatsu, Masamichi; Sako, Hideki; Hashimoto, Ai; Sugie, Ryuichi; Honda, Yoshio; Amano, Hiroshi; Kojima, Kazunobu; Chichibu, Shigefusa F.
Abstract: Energy-dispersive X-ray signals calibrated by Rutherford backscattering indicated the generation of Al13/24 Ga11/24 N in Ga-rich stripes in a nonflat Al0.58 Ga0.42 N layer. Also, the CL peak wavelengths of ∼259 and 272 nm also showed the generation of Al15/24 Ga9/24 N and Al13/24 Ga11/24 N in Al-rich zones and Ga-rich stripes, respectively. The wavelength of a strong CL peak at ∼246 nm, which was observed from the Al0.7 Ga0.3 N layer in our previous study, is also considered to correspond to the near-band-emission wavelengths of Al17/24 Ga7/24 N. In particular, the stronger reproducibility of metastable Al15/24 Ga9/24 N generation was confirmed, in agreement with the computed predictions by other research groups.